2018
DOI: 10.1097/qad.0000000000001790
|View full text |Cite
|
Sign up to set email alerts
|

In-utero exposure to antiretrovirals and neurodevelopment among HIV-exposed-uninfected children in Botswana

Abstract: Neurodevelopmental outcomes at 24 months of age were similar in ART-exposed vs. ZDV-exposed HEU children. Maternal ART with breastfeeding does not appear to have an adverse effect on neurodevelopment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 33 publications
2
22
0
Order By: Relevance
“…In a US cohort study, language outcomes were affected by specific antiretrovirals (including atazanavir associated with late language emergence at 1 year of age and tenofovir with speech impairment at 3 years but not 5 years of age) 19 . In Botswana, no effect of monotherapy versus triple ART therapy on developmental outcomes was observed, 27 although efavirenz exposure was associated with lower receptive language scores at 2 years of age compared with non-efavirenz-containing therapies 28 . A study from Uganda and Malawi found no increased developmental risk associated with maternal ART 8 .…”
Section: Discussionmentioning
confidence: 99%
“…In a US cohort study, language outcomes were affected by specific antiretrovirals (including atazanavir associated with late language emergence at 1 year of age and tenofovir with speech impairment at 3 years but not 5 years of age) 19 . In Botswana, no effect of monotherapy versus triple ART therapy on developmental outcomes was observed, 27 although efavirenz exposure was associated with lower receptive language scores at 2 years of age compared with non-efavirenz-containing therapies 28 . A study from Uganda and Malawi found no increased developmental risk associated with maternal ART 8 .…”
Section: Discussionmentioning
confidence: 99%
“…30 Additionally, neurodevelopmental outcomes of HEU children perinatally exposed to 3-drug ART were similar to those exposed to zidovudine monotherapy. 31…”
Section: Discussionmentioning
confidence: 99%
“…Studies included in the present review also considered the relationships between child development and malaria or HIV (five studies on malaria and 11 studies on HIV). Malaria studies focused primarily on cognitive development ( 44‐47 ) , whereas HIV studies incorporated both cognitive and motor development ( 29,42‐52 ) .…”
Section: Resultsmentioning
confidence: 99%